Peningkatan Hasil Belajar Akidah Akhlak Melalui Penggunaan Media Video Pembelajaran Daring Pada Siswa Kelas VII MTS Negeri 3 Pekanbaru - Murni, Tuti (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This study aims to improve student learning outcomes in the Akidah Akhlak subject through the use of video media for class VII.1 at MTs Negeri 3 Pekanbaru City. The problem raised is that Student Learning Outcomes in Akidah Akhlak Subjects Can Improve Through the Use of Online Learning Video Media for class VII.1 at MTs Negeri 3 Pekanbaru City. The design or design in this research is Classroom Action Research (CAR). CAR is